Forensic science policy and the question of governmental University research quality assessment - Evison, Martin Paul (Forensic science international, 2018)
•Summary of research outputs submitted in forensic cognate disciplines in RAE2008 and REF2014.•Assessment of the value of these exercises in the audit of University research quality in forensic science.•Discussion of policy and implications for forensic science research quality assessment. Forensic science policy has been the subject of a series of judicial and parliamentary enquiries in the United Kingdom in recent decades. Forensic science research has been a recurrent theme in their reports, which have included recommendations for research into the economics of forensic service provision; for the development of expertise and centres of excellence; and for research to establish the validity of the forensic sciences. These recommendations reflect similar concerns expressed internationally—particularly in the United States. In the United Kingdom, however, the Forensic Science Service recently enjoyed a near monopoly in research, and limited research funding and activity in the Universities was exacerbated by the lack of visibility of forensic science in government audits of research quality. This study used established methods in evidence-based policy and research quality evaluation to analyse the range, quantity and quality of research submitted to the two most recent audits—RAE 2008 and REF 2014. Strengths and weaknesses in the methods used are discussed, and the findings analysed in relation to wider research policy issues in forensic science. The study concludes that consolidating forensic science as a peer-science in the academy is essential in order to establish a virtuous circle that will sustain research in the discipline—and address wider policy and socio-economic questions that persistently trouble the field.